Discussing Race in American Professional Sport: The Case of Mixed-Race Athletes Tiger Woods and Colin Kaepernick - Nathalie Loison (Revue LISA)
In the late 1990s, the United States Census Bureau considered the idea of adding a “multiracial” category on the 2000 census forms to quantify the new multiracial population which was believed to have increased. In the context of this American “post-racial” period characterized by the supposed end of racism, mixed-race golfer Tiger Woods and football player Colin Kaepernick addressed the subject of race at the beginning of their careers. In 1997, Woods refused to be defined as black and used the self-invented word “Cablinasian” to encapsulate his racial mixing. In 2016, Colin Kaepernick did not stand up when the national anthem was played during a pre-season match in order to object to racial injustice in the United States. This article aims to analyze the public images of Tiger Woods and Colin Kaepernick as racial constructs. It interrogates their discourse on the notion of race – as well as their potential complicity with the media’s construction of their image – to sketch the outline of their possible racial identity. Putting Woods and Kaepernick’s discourses on race in historical perspective will show that their media image builds on the athletes’ need to frame their narrative into the political debates of their times.